Urbanization increased annual precipitation in temperate climate zone: A case in Beijing-Tianjin-Hebei region of North China - Tao Sun (Elsevier, 2021)
Rapid urbanization plays important roles in modifying regional climate. The effects of urbanization on annual precipitation in temperate climate zone were complicated and have not been fully investigated. In this study, Beijing-Tianjin-Hebei (BTH) region of North China was selected as research area and field observations of inter-annual precipitation from 1980 to 2015 were utilized to conduct the spatiotemporal analysis and to extract the urbanization effects. Combined statistical methods were applied and the urbanization effects indicator (UE) was created to quantify the roles of urban development on annual precipitation by combining the land cover change of cities and urban–rural precipitation differences. The paper found following main results: (1) In 2000 s, annual precipitation increased faster in urban areas (slope = 7.165 mm/yr) than in rural areas (slope = 4.954 mm/yr). The urbanization effects on the increasing of precipitation have been implied by comparisons of urban–rural difference between 2000 s (slope = 2.211 mm/yr) and 1980 s (slope = 0.165 mm/yr). (2) Rapid urbanization led to increasing of annual precipitation. Built-up areas correlated higher with urban precipitation than with rural precipitation in 9 of 13 cities, and were used as weights to improve the urbanization effects indicator (UE). (3) As the largest and the most developed city, Beijing presented the highest urbanization effects (UE = 44.5) on the increasing inter-annual precipitation, which was 51% higher than the secondary city of Chengde (UE = 21.71). The coastal cities such as Tianjin, Qinhuangdao and Tangshan presented negative UE values probably due to the strong sea-land energy interactions. This study contributes new findings to the effects of urbanization on annual precipitation in temperate climate zone and could help understand the feedback of land surface changes to variations of atmospheric circulation.